A new cassane diterpenoid from the seeds of Caesalpinia decapetala. Issue 4 (2nd April 2016) - Wei, Hua; Liu, Xiao-Qian; Zhu, Jing-Jing; Gao, Liang-Liang; Wang, Zhi-Min; Yan, Li-Hua
Abstract : Phytochemical investigation on the seeds of Caesalpinia decapetala led to the isolation of a new cassane diterpenoid with an unusual O bridge between C-19 and C-20, named phanginin Q (1 ), together with three known cassane diterpenoids, caesaljapin (2 ), caesaldekarin A (3 ), and caesaldekarin B (4 ). The structure of the new compound was elucidated by spectroscopic methods, including 1 H NMR, 13 C NMR, HSQC, 1 H − 1 H COSY, HMBC, NOESY, and HR-ESI-MS.